Three Experiences, A Global Perspective (Journal of Parents and Teachers, 2025)
Three education students share their experiences in international teaching settings: a camp in the United States, a training stay in Germany and an intensive program in the Netherlands. Through these diverse experiences, each student encountered new cultures, educational methods and values, deepening their understanding of the transformative potential of global education, the role of empathy in teaching, and the value of shared learning beyond the classroom.
Keywords: education; teaching education; internationalization; multiculturalism; innovation